Cultural property : law, policy, and markets / Amnon Lehavi. - Lehavi, Amnon (Global law series., 2026)
While nations, societies, and individuals have always been engaged with both the tangible and intangible aspects of cultural objects, such as archaeological artifacts, artworks, and historical documents, the twenty-first century is seeing a significant shift in the law, ethics, and public policy that have long characterized this field. This book offers a comprehensive analysis of recent developments concerning cultural property. It identifies the underlying forces that drive these changes, focusing on the new political balance between source countries and market countries, the strengthening of cross-border lawmaking and law enforcement, the growing impact of provenance research and due diligence as legal, professional, and ethical norms, and the transformative role of digital databases. The book sets out normative principles for designing a better synergy of the hard law and soft law mechanisms that govern cultural property policy and markets. It proposes a property theory of ownership and custody of cultural objects and outlines a model of 'new cultural internationalism' to promote cross-border collaboration on cultural heritage, including new restitution frameworks.